Computational analysis of 3D biopolymeric porous scaffolds for the in vitro development of neural networks - Ilaria Parodi; Laura Pastorino; Giacomo Damonte; Silvia Scaglione; Marco Massimo Fato; Donatella Di Lisa (PLoS ONE, 2025)
Computational modelling can be used to study and improve specific experimental tissue engineering protocols and outcomes. Proper oxygenation and nutrient substances supply such as glucose are crucial in 3D in vitro models. In most cases, hydrogel-based scaffolds are employed as culture systems. However, the diffusion of molecules could be difficult in the innermost areas of the scaffolds, and the presence of gradients could affect cell proliferation, especially in static conditions. Hence, the mathematical modelling of oxygen and nutrient transport, as well as their consumption by the expanding cell culture within the scaffold, can be useful for optimizing tissue construct properties and generating more predictive and robust outcomes. In this work, nutrient diffusion has been studied through two different scaffolds seeded with glial and neuronal cells: chitosan microbeads and PLA fibers covered in chitosan produced with two specific fabrication-based techniques. First, homogenization theory has been applied to the two different porous constructs, formulated as heterogeneous domains composed of two distinct phases: the culture medium and the polymeric material. Then, a continuous mathematical model of nutrient transportation-consumption and cell proliferation has been implemented in COMSOL, aiming to comprehend nutrient diffusion to allow suitable environmental conditions for the growth of neural cells on 3D biopolymeric scaffolds.